Ferroelectric Polymer Composites and Evaluation of Their Properties; Handbook of Smart Manufacturing: Forecasting the Future of Industry 4.0 - Lebedev S. M. Sergey Mikhailovich (2023, 2023)
This chapter presents the results of a study of ferroelectric polymer composites with a high permittivity. To produce these ferroelectric composites, polymer matrices such as polyethylene, elastomers, polyvinylidene fluoride, and poly(lactic acid) filled with ferroelectric ceramic powders were applied in the given work. Ferroelectric ceramic powders of lead zirconate titanate (PZT) and barium titanate (BT, BaTiO3) with a powder particle size not more than 1 μm were used as fillers in this work. It is shown that the filling of polymer matrices with ferroelectric ceramics powders with a high permittivity allows dielectric, mechanical, and rheological properties of composites to be significantly improved. The experimental data of dielectric spectroscopy in the frequency domain correlate well with the SEM microscopy analysis from the viewpoint of the percolation theory